2017
DOI: 10.1016/j.apsb.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

In vivo retention of poloxamer-based in situ hydrogels for vaginal application in mouse and rat models

Abstract: The purpose of this study is to evaluate the in vivo retention capabilities of poloxamer-based in situ hydrogels for vaginal application with nonoxinol-9 as the model drug. Two in situ hydrogel formulations, which contained 18% poloxamer 407 plus 1% poloxamer 188 (GEL1, relative hydrophobic) or 6% poloxamer 188 (GEL2, relative hydrophilic), were compared with respect to the rheological properties, in vitro hydrogel erosion and drug release. The vaginal retention capabilities of these hydrogel formulations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Conventional vaginal medicinal forms include suppositories, films, effervescent tablets, capsules, vaginal rings, and semisolid preparations, such as hydrogels and foams. Due to the ease of administration and their flexibility, semisolid forms such as hydrogels are much more popular than solid formulations [ 89 , 129 ]. However, vaginal drug delivery is often limited because of the protective mechanisms of the vagina, including a wide range of physiological characteristics including pH variation, microflora, and cervical mucus.…”
Section: Poloxamer 407-based Mucoadhesive Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional vaginal medicinal forms include suppositories, films, effervescent tablets, capsules, vaginal rings, and semisolid preparations, such as hydrogels and foams. Due to the ease of administration and their flexibility, semisolid forms such as hydrogels are much more popular than solid formulations [ 89 , 129 ]. However, vaginal drug delivery is often limited because of the protective mechanisms of the vagina, including a wide range of physiological characteristics including pH variation, microflora, and cervical mucus.…”
Section: Poloxamer 407-based Mucoadhesive Formulationsmentioning
confidence: 99%
“…The development of mucoadhesive pharmaceutical formulations that have the ability to efficiently interact with the mucosal tissue of the vagina offers the possibility of prolonging the therapeutic effects of a drug, improving patient compliance, and decreasing the number of administrations necessary [ 127 ]. Thermo-sensitive hydrogels characterized by a gelation process that takes place in the vaginal lumen would favor a prolonged residence time of the drugs they contain [ 129 ]. They would form a protective layer on the surface of the vaginal mucosa, which is useful in the treatment of local vaginal infections, such as candidiasis, or for contraception through the inhibition of sperm motility [ 3 , 127 , 129 ].…”
Section: Poloxamer 407-based Mucoadhesive Formulationsmentioning
confidence: 99%
“…Poloxamers are biodegradable by erosion [57] and biocompatible polymers [58]. Based on these safety data and the information that the manufacturing process can be controlled to limit unwanted impurities, the Cosmetic Ingredient Review Expert Panel concluded that poloxamers are safe as used [59].…”
Section: Preparation Of In Situ-forming Gelmentioning
confidence: 99%
“…Poloxamer (such as F127 and F68) could be designed as the thermosensitive contraceptive vaginal hydrogel for in situ loading curcumin for contraception [33][34][35]. Wei et al designed the poloxamer-based in situ vaginal hydrogels with loading nonoxynol-9 as a model drug, different poloxamer 407/poloxamer 188 ratios were used for adjusting hydrophilic content of hydrogel formulations, and further regulating hydrogels erosion, drug release, and intravaginal elimination [36]. The poloxamer with the clotrimazole loaded nanostructured lipid carriers could be diluted with simulated vaginal fluid (SVF) to form thermo-hydrogels for treating fungal vaginal infections [37].…”
Section: Introductionmentioning
confidence: 99%